Corrections to “Impact of Artificial Intelligence in Nursing for Geriatric Clinical Care for Chronic Diseases: A Systematic Literature Review” - Mahdieh Poodineh Moghadam; Zabih Allah Moghadam; Mohammad Reza Chalak Qazani; Pawel Plawiak; Roohallah Alizadehsani (IEEE Access)
Presents corrections to the paper, (Corrections to “Impact of Artificial Intelligence in Nursing for Geriatric Clinical Care for Chronic Diseases: A Systematic Literature Review”).